2018
DOI: 10.1016/j.envpol.2018.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Radiocesium concentrations in soil and leaf after decontamination practices in a forest plantation highly polluted by the Fukushima accident

Abstract: Owing to the Fukushima Dai-ichi Nuclear Power Plant (FDNPP) accident a vast amount of radiocesium was released polluting the land. Afterwards, a variety of decontamination practices has been done, reducing the ambient dose rates. In this study we evaluated the effectiveness of eight forest decontamination practices by means of monitoring the radiocesium (Cs) concentration in soil and leaf samples, and the daily discharge rates in ten plots during 27 months (May 2013-July 2015). A forest plantation located 16 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In general, owing to the strong and nearly irreversible bond of radiocesium to fine soil particles, the majority of FDNPPderived 137 Cs is stored within the topsoil (i.e. the top 5 cm) in undisturbed soils (Lepage et al, 2014;Matsuda et al, 2013Matsuda et al, , 2015Takahashi et al, 2015;Mishra et al, 2015). Mishra et al (2015) reported that for these undisturbed soils, the vertical migration of radiocesium down the soil profile was slower in forest soils compared to grassland soils.…”
Section: Radiocesium Distribution With Depth In the Soilmentioning
confidence: 99%
“…In general, owing to the strong and nearly irreversible bond of radiocesium to fine soil particles, the majority of FDNPPderived 137 Cs is stored within the topsoil (i.e. the top 5 cm) in undisturbed soils (Lepage et al, 2014;Matsuda et al, 2013Matsuda et al, , 2015Takahashi et al, 2015;Mishra et al, 2015). Mishra et al (2015) reported that for these undisturbed soils, the vertical migration of radiocesium down the soil profile was slower in forest soils compared to grassland soils.…”
Section: Radiocesium Distribution With Depth In the Soilmentioning
confidence: 99%
“…CC BY 4.0 License. (Lepage et al, 2015;Matsunaga et al, 2013). For example, Lepage et al (2015) illustrated that 90% of the FDNPP derived radiocesium was homogeneous throughout the tilled soil layer in cultivated soils.…”
Section: Strategies For Decontamination In Various Environments and mentioning
confidence: 99%
“…(Lepage et al, 2015;Matsunaga et al, 2013). For example, Lepage et al (2015) illustrated that 90% of the FDNPP derived radiocesium was homogeneous throughout the tilled soil layer in cultivated soils. Endo et al (2013) reported that radiocesium concentrations were not depth dependent in cultivated soils (i.e.…”
Section: Strategies For Decontamination In Various Environments and mentioning
confidence: 99%
“…exposure, appropriate shielding materials are compulsory. For instance, as a fission product of 235 U, 137 Cs radioactive isotope, which emits high energy β -particles and γ -rays (charge = 0, rest mass = 0), highly contaminates the surrounding environment (water, soil, air) once any nuclear reactor accident occurs (e.g., Fukushima Daiichi Nuclear Power Plant (FDNPP) accident, Japan, 2011) [ 1 ]. In humans, external exposure to 137 Cs (in greater amounts) can cause radiation burns, acute radiation sickness (ARS), coma, and even death, while internal exposure through inhalation/ingestion increases cancer (abnormal growth in cells) risk.…”
Section: Introductionmentioning
confidence: 99%